Osteoarthritis and risk of hospitalization for ambulatory care-sensitive conditions: a general population-based cohort study. (16th February 2021) - Kiadaliri, Ali; Englund, Martin
Abstract: Objective: To determine the association between OA and risk of hospitalization for ambulatory care-sensitive conditions (HACSCs). Methods: We included all individuals aged 40–85 years who resided in Skåne, Sweden on 31 December 2005 with at least one healthcare consultation during 1998–2005 ( n  = 515 256). We identified those with a main diagnosis of OA between 1 January 1998 and 31 December 2016. People were followed from 1 January 2006 until an HACSC, death, relocation outside Skåne, or 31 December 2016 (whichever occurred first). OA status was treated as a time-varying covariate (those diagnosed before 1 January 2006 considered as exposed for whole study period). We assessed relative [hazard ratios (HRs) using Cox proportional hazard model] and absolute (hazard difference using additive hazard model) effects of OA on HACSCs adjusted for potential confounders. Results: Crude incidence rates of HACSCs were 239 (95% CI: 235, 242) and 151 (150, 152) per 10 000 person-years among OA and non-OA persons, respectively. The OA persons had an increased risk of HACSCs [HR (95% CI) 1.11 (1.09, 1.13)] and its subcategories of medical conditions except chronic obstructive pulmonary disease [HR (95% CI) 0.86 (0.81, 0.90)]. There were 20 (95% CI: 16, 24) more HACSCs per 10 000 person-years in OA compared with non-OA persons. While HRs for knee and hip OA were generally comparable, only knee OA was associated with increased risk of hospitalization for diabetes. Conclusion: OA is associated with an increased risk of HACSCs, highlighting the urgent need to improve outpatient care for OA patients.